Anatomical Variations of Renal Artery in Patients Undergoing Computed Tomography of Abdomen: A Hospital-based Cross-sectional Study - Chhetri, Pramod Kumar; Basnet, Prabhat; Adhikari, Aarati (Journal of Lumbini Medical College, 2021)
Introduction: Renal vasculature is known for presenting a wide range of variations. Knowledge of different anatomical variations helps the surgeon prevent possible intraoperative complications. Computed Tomography (CT) is an excellent imaging modality providing detailed anatomy of the renal artery. This study aimed to evaluate renal arterial variations in individuals undergoing abdominal CT examination. Methods: This was a hospital based cross-sectional study on 400 consecutive patients who underwent abdominal CT examination in a medical college in Nepal. The number of patients with normal and any arterial variations was noted. Accessory renal artery (hilar and polar artery) and any pre-hilar branching were evaluated. Results: Among 400 patients, 271 (67.75%) individuals had normal renal artery supply and 129 (32.25%) had variations. Among 129 individuals (79 males and 50 females) with artery variations, 93 (72.09%) had unilateral and 36 (27.91%) had bilateral variations. The most common unilateral variation was a single polar artery in 66 (70.97%) cases, pre-hilar branching in 18 (19.35%), accessory hilar artery in 7 (7.53%) and dual polar arteries in 2 (2.15%). In those with bilateral arterial variations, the right and left kidneys showed polar artery in 25 (69%) and 30 (83%), pre-hilar branching in 6 (17%) and 2 (6%), and accessory hilar in 5 (14%) and 4 (11%) cases respectively. Conclusion: Renal artery variation was observed in approximately one-third of individuals. Unilateral variation was more common than bilateral and polar artery was the most common arterial variant.